Antibacterial Activity of Red yeast rice Extract against Propionibacterium acnes ATCC 11827 and Methicilin-Resistant Staphylococcus aureus ATCC BAA-1683 - Tiana Milanda; Ade Zuhrotun; Ulya Nabila; Vesara A. Gathera; Arif S.W Kusuma (Pharmacology and Clinical Pharmacy Research, 2021)
Propionibacterium acnes ATCC 11827 and Methicillin-Resistant Staphylococcus aureus ATCC BAA-1683 are bacteria that cause skin infections, namely acne vulgaris and skin and soft tissue infection/SSTI. The increase in the number of resistant bacterial strains, such as MRSA,  requires the search for alternative antibiotics, including using natural ingredients. Red yeast rice is a product of rice fermentation by Monascus purpureus, which is known to have antibacterial, antifungal, antitumor, antioxidant, anti-inflammatory, anti-cholesterol and immunomodulator. This study aims to determine the antibacterial activity of several red yeast rice extracts against these bacteria that cause skin infections. The research was carried out through the stages of collecting materials and identifying the yeast isolates, extracting of red yeast rice, phytochemical screening of red yeast rice extract, confirmation of bacterial test, preparation of bacterial test suspension, testing for bacterial resistance, testing for antibacterial activity of red yeast rice extract and determining the value of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the most active extract. The results showed that the ethyl acetate and ethanol extracts had antibacterial activity against P. acnes ATCC 11827 and MRSA ATCC BAA-1683. Both extracts contain compounds from the polyphenols, flavonoids, quinones and saponins group. Ethyl acetate extract was the most active extract with MIC values against P. acnes ATCC 1182 and MRSA ATCC BAA-1683 of 50 mg/mL and 12.5 mg/mL. The MBC values of ethyl acetate extract against these bacterial tests were 100 mg/mL and 25 mg/mL. The ethyl acetate extract is more active against MRSA ATCC BAA-1683 than against P. acnes ATCC 11827. From the results of this study it is known that red yeast rice has activity against bacteria that cause skin infections, especially against MRSA